PEMBENTUKAN KARAKTER KEBANGSAAN PESERTA DIDIK MELALUI EKSTRAKULIKULER PRAMUKA DI MINU MAUDLU’UL ULUM MALANG - Lailatul Musharrofah; Anwar Sa’dullah; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Abstrac The formation and development of character from an early age is very necessary, therefore it is not only necessary to swallow learning in the classroom but in the classroom, scouting is the right extracurricular for character building especially national character so that students can have the spirit of nationalism through the practice of darma. Scout extraculicular activities carried were held every Saturday with alternating between standby scouts and mobilixing and efforts in forming national character trough scouting activites,the impotance of education to direct students to develop character positive in boyh the scope of religion, and nationalism by practicing character values in everyday life. In this study using a method with 3 instruments, namely: interview, observation and documentation. This study also aims to describe: 1) scout extracurricular activities, 2) efforts to establish national character. And the results of this study show that broadly the character of the nationality of students at MINU Maudlu’ul Ulum is classified as student who are easily directed and conditioned by the spirit of the ceremony held before and after the scout extra curricular activites. The number of standby scout students in one class so that the coach has difficulty to condition class.Keywords: Nationality character, Extracurricular, Scout